PERLINDUNGAN HUKUM BAGI NASABAH DALAM LIKUIDASI BANK - Ciria Angga Mahendra, Made; -, Yuwono (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015, 2015)
Banks as financial institutions which can directly withdraw funds from the public needspecial arrangements. In for the bank in carrying out its activities should always refer to thelegislation governing banks as financial services. For that to know the steps or policies that needto be taken in order to protect against the Customer in banking which went into liquidation.Contained in a presidential decree Number 2 of 2008 on Deposit Insurance Corporation. Giventhat the customer is using the bank's business, then the protection of customers it's time is done.Thus it is necessary we need to ketahaui about protection for customers. The purpose of thispaper is to determine the form of legal protection for the customers in the bank liquidation.Method which used in this paper covers methods of normative principles study of hukum.conclusions that can be drawn in this paper is: customers can protect themselves in two ways:implicitly protection and protection explicit.
Keywords: Protection, Customer, Bank Liquidation